Beyond cigarette smoking: smoke-free home rules and use of alternative tobacco products. (January 2016) - Zhang, Xiao; Martinez-Donate, Ana P; Kuo, Daphne; Piper, Megan
Background: A smoke-free home rule has been associated with reduced cigarette consumption; however, it is unknown whether a home rule is associated with the use of alternative tobacco products (ATP) such as smokeless tobacco products, regular and water pipes, and cigars. This study examined the association between the smoke-free home rules and ever and current use of ATP. Method: Data from the 2010–2011 US Tobacco Use Supplements to the Current Population Survey were analysed using multivariable logistic regressions, including variables related to smoke-free home rules. Results: Overall, 83.9% respondents reported a smoke-free home rule inside their homes; 20.6% of respondents had tried at least one type of ATP, and 3.9% were current users in 2010–2011. Having a smoke-free home rule was associated with lower likelihood of current versus never use of any ATP (adjusted odds ratio (AOR) = 0.80, 95% confidence interval (CI): 0.77–0.83). Among ever users of any ATP, the existence of a smoke-free home rule was associated with lower odds of being a current user (AOR = 0.49, 95% CI: 0.43–0.56). Similar associations were observed for each type of ATP examined (p < 0.05). Conclusion: Smoke-free home rules are associated with lower current ATP use among the US population. Future research should examine whether promoting smoke-free home rules could help to reduce ATP use and related diseases.